Morphological characteristic and nutritional status in seven-year-old girls - Đorđević Marija M.; Kostić Radmila M. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2015)
Nutritional status of children is one of the most important indicators of health, mental and physical capabilities and potential for normal and healthy growth and development. The aim of this study was to determine differences in morphological characteristics in seven-year-old girls with varying degrees of nutritional status. The research was conducted on a sample of 88 first grade students of elementary schools in Niš, aged 7.07 (±0.5). Based on the BMI, three sub-samples were formed (normal weight, overweight and obese subjects). Morphological status was determined by measuring the parameters of longitudinal, transversal and circulardimensionality, body weight andsubcutaneous fatty tissue. Differences in morphological variables were determined by using MANOVA/ANOVA and LSD Post Hoc test. The results indicate that, in regards to the BMI, there are significant differences in morphological characteristics in seven-year-old girls. Higher values of morphological characteristics were recorded in overweight and obese subjects.